The first species of Siamites Franz (Coleoptera, Staphylinidae, Scydmaeninae) in East Malaysia - Jałoszyński, Paweł (Zootaxa, 2019)
The glandulariine genus Siamites is amongst the rarest Oriental ant-like stone beetles. To date, only three species have been known, distributed in Thailand and Vietnam. A new species, S. sarawakensis sp. n. is described here, based on a male specimen collected in Sarawak, East Malaysia. This finding extends the known range of Siamites over 1200 km southeastward.